2015
DOI: 10.5455/ijlr.20150717102356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed and Health Packages on the Performance of Village Small Ruminants in Northern Ghana

Abstract: The objective of this study was to assess the productivity of small ruminant through the introduction of improved healthcare and feeding strategies into small ruminant production systems. The General Linear Model of SAS was used to compare means after fitting sources of variation to models. Growth rate of treatment animals was higher than that of control animals (P<0.05). Lambs grew about twice as fast as kids (P<0.05). Lower mortality rate was observed in treatment animals compared to control (P<0.05), partly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The ADG values for sheep and goats in the control and treatment groups were similar to those reported by Avornyo et al (2015) for sheep and goats, and by Konlan et al (2017) for sheep in studies on feed supplementation and provision of healthcare (17.8 and 45.4 g/day for sheep under control and healthcare, respectively). The live weights of goats and sheep at 3 and 12 months in our study were lower than those and Ayantunde, 2014) and they generally have a high crude protein content, but they are high in lignin content which limits intake and digestibility.…”
Section: Body Weight Development and Growthsupporting
confidence: 79%
See 2 more Smart Citations
“…The ADG values for sheep and goats in the control and treatment groups were similar to those reported by Avornyo et al (2015) for sheep and goats, and by Konlan et al (2017) for sheep in studies on feed supplementation and provision of healthcare (17.8 and 45.4 g/day for sheep under control and healthcare, respectively). The live weights of goats and sheep at 3 and 12 months in our study were lower than those and Ayantunde, 2014) and they generally have a high crude protein content, but they are high in lignin content which limits intake and digestibility.…”
Section: Body Weight Development and Growthsupporting
confidence: 79%
“…Ba et al (1996) reported similar results in Mali when introducing health treatment alone. Konlan et al (2017), and Avornyo et al (2015) also reported synergistic benefits of the combined effect of providing concentrate feed and healthcare to small ruminants kept by smallholder farmers in Northern Ghana.…”
Section: Flock Structure and Dynamicsmentioning
confidence: 93%
See 1 more Smart Citation
“…These treatments were performed to clear the experimental animals of any bacterial and parasitical infections, and standardize their health condition prior to the commencement of the experiment. Previous studies (Avornyo et al 2015) have shown evidence of the effectiveness of the medicines used. The goats were individually housed in metabolism cages measuring 60 cm by 70 cm and 70 cm high, and equipped with feeding and water troughs.…”
Section: Experimental Design Animals and Treatmentsmentioning
confidence: 95%